Covid-19: Economic Policy Interventions Across Continents - Lucas Perasolo; Daria Schaller; Tanja Stitteneder; Madhinee Valeyatheepillay (CESifo Forum, 2020)
Coronavirus has changed the way we live and work in many ways and has presented hurdles for businesses and individuals. Countries around the world have taken action to help their economies overcome the crisis and have applied various measures to stimulate the economy by supporting businesses and individuals. Although the approaches are similar, many measures differ in their precise design and their implementation. This article presents some recent fiscal policy measures in terms of public spending, taxes, and other financial support in eight countries, including Australia, Brazil, China, Germany, Italy, South Africa, Sweden and the US.
Keywords: 330